Periocular Chemotherapy in Palpebral Malignancies: A Review - Nabita Aulia; Halimah Pagarra; Suliati P Amir; Andi Pratiwi (Jambura Medical and Health Science Journal, 2023)
Background: Palpebral malignancy is still a significant health problem and consists of sebaceous gland carcinoma (SGC), basal cell carcinoma (BCC), squamous cell carcinoma (SCC), and malignant melanoma (MM). Although total resection using the Moh micrograph method is standard therapy for these cases, perioral chemotherapy may be an alternative therapy in patients where surgery cannot be performed.Content: Periocular chemotherapy in lid malignancy is recommended in cases that are inhibited or contraindicated for surgery, with obscure tumor margins, with markers of tumor invasion of vascular, lymphatic, nerve, or other orbital structures, signs of relapse after surgery, local pagetoid involvement, sizeable tumor size, and also presented an appearance of diffuse and multifocal tumor on histopathological examination. Choices of local chemotherapeutic agents based on the variety of palpebral malignancy, namely: (1) imiquimod for BCC; (2) mitomycin-C for SGC; (3) cisplatin, doxorubicin, bleomycin, peplomycin, methotrexate, and 5-fluorouracil for SCC; and (4) Imiquimod for MM. Topical chemotherapy is given to patients using an iodontotherapy method or ophthalmic cream.. More often than not, topical chemotherapy possessed a few side effects that are mild and tolerable and disappear on their own after treatment has finished.Conclusion: Local/periocular chemotherapy for palpebral malignancy is an alternative adjuvant therapy that can be considered, especially in cases where surgery is not possible. Key words: Malignancy, chemotherapy, palpebral, periocular